“Delo Tutumulo Lambi” As a Form of Income Accounting Practice in Pesantren: Islamic Ethnomethodology - Thalib, Mohamad Anwar; Harun, Fadila M.; Hanasi, Syaila Mulyani (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
This study is driven by income accounting theory in Islamic boarding schools, which has focused on technical aspects and appears separate from local cultural values and religiosity. This research is important for preserving pesantren accounting practices based on local wisdom. The question posed is: how do pesantren managers practice income accounting, and how are local cultural values reflected in this practice? The novelty lies in the study of income accounting for Islamic boarding schools based on local cultural values and religiosity. The paradigm used is spiritual with an Islamic ethnomethodology approach. Data was analyzed thru five stages: charity, knowledge, faith, revealed information, and courtesy. The type of qualitative method used. The findings is four income accounting practices: income sourced from tuition fees and external party assistance, income sourced from land rental, using income for pesantren operational activities, and a simple method of income recording. This practice reflects the local cultural value of delo tutumulo lambi, which means a life that benefits many people. This study concludes that income accounting in Islamic boarding schools is not just an economic record, but also a spiritual practice that reflects local culture. Practically, this helps managers develop more contextual and value-based accounting systems. Theoretically, this enriches accounting literature with cultural and spiritual perspectives.